Anti‐inflammatory effects of the GAG‐binding CXCL9(74‐103) peptide in dinitrofluorobenzene‐induced contact hypersensitivity in mice. Issue 10 (14th August 2018) - Vanheule, Vincent; Crijns, Helena; Poosti, Fariba; Ruytinx, Pieter; Berghmans, Nele; Gerlza, Tanja; Ronsse, Isabelle; Pörtner, Noëmie; Matthys, Patrick; Kungl, Andreas J.; Opdenakker, Ghislain; Struyf, Sofie; et al.
Summary: Background: To recruit leucocytes to an inflammatory site, chemokine binding to glycosaminoglycans (GAGs) is critical. Therefore, strategies to interfere with this interaction, aiming at the production of anti‐inflammatory agents, were developed. These include production of modified chemokines without affinity for G protein‐coupled receptors but with enhanced affinity for GAGs. Such modified chemokines compete with functional chemokines for GAG binding, prevent chemokine immobilization and presentation, and inhibit leucocyte migration. In addition to modified chemokines, a GAG‐binding peptide consisting of the 30 COOH‐terminal residues of CXCL9, that is CXCL9(74‐103), inhibited CXCL8‐ and monosodium urate crystal‐induced neutrophil migration. Objective: We wanted to explore whether interference with chemokine‐GAG interactions by CXCL9(74‐103) reduces inflammation in neutrophil‐dependent dinitrofluorobenzene‐induced contact hypersensitivity. Methods: For this study, we evaluated several inflammatory parameters, including ear swelling and the levels of chemokines, cytokines, proteases and neutrophils in the ears of dinitrofluorobenzene‐induced mice treated with CXCL9(74‐103) or buffer. Results: One intravenous injection of CXCL9(74‐103), just before painting with dinitrofluorobenzene on the ear, did not affect protein levels of the major murine neutrophil attractant, that is CXCL6, in this contact hypersensitivity model. However, IL‐6, CXCL1, CCL2 and matrix metalloproteinase‐9 (MMP‐9) protein concentrations and peroxidase activity in challenged ears were reduced. In addition, intravenous injection of the CXCL9‐derived peptide led to a reduced ear swelling response, indicating that the locally produced chemokines were hindered to attract leucocytes. The inhibiting potential of CXCL9(74‐103) was explained by its competition for GAG binding with CXCL1, CXCL6 and CCL3 and inhibition of transendothelial migration of neutrophils to CXCL6. Conclusions and Clinical Relevance: The CXCL9(74‐103) peptide inhibited dinitrofluorobenzene‐induced infiltration of neutrophils and neutrophil‐dependent inflammation in ears. Therefore, CXCL9(74‐103) may be a lead molecule for the development of therapeutic peptides or peptide derivatives that compete with functional chemokines for GAG binding.